2015
DOI: 10.1007/s12161-015-0253-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Voltammetric Determination of Synthetic Colorants in Foods Using a Magnetic Core–Shell Fe3O4@SiO2/MWCNTs Nanocomposite Modified Carbon Paste Electrode

Abstract: This paper reports the production of a novel magnetic nanocomposite based on multi-walled carbon nanotubes (MWCNTs) decorated with magnetic coreshell Fe 3 O 4 @SiO 2 nanoparticles which were used to f a b r i c a t e a m o d i f i e d c a r b o n p a s t e e l e c t r o d e (Fe 3 O 4 @SiO 2 /MWCNT-CPE). The Fe 3 O 4 @SiO 2 / MWCNT-CPE was investigated for the simultaneous determination of sunset yellow (SY) and tartrazine (TT) in 0.1 mol/L phosphate buffer solution (pH 6.0) using square wave voltammetry (SWV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Therefore, various electrochemical approaches have been developed for the individual and simultaneous determination of these dyes [17][18][19]. Most of these approaches use chemically-modified electrodes based on nanomaterials [18]: carbon nanomaterials [20][21][22][23][24], metal [25,26] and metal oxide nanoparticles [27][28][29][30], as well as their composites and combinations [31][32][33][34][35], including graphene wrapped-phosphotungstic acid hybrid [36], and the combination of reduced graphene oxide with metal-organic frameworks of Ni with 1,3,5-benzene tricarboxylic acid [37]. An original approach for the simultaneous quantification of sunset yellow FCF and tartrazine has recently been developed using a paper-based electrode (conductive ink based on graphite powder and nail polish supported on cardboard) [38].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various electrochemical approaches have been developed for the individual and simultaneous determination of these dyes [17][18][19]. Most of these approaches use chemically-modified electrodes based on nanomaterials [18]: carbon nanomaterials [20][21][22][23][24], metal [25,26] and metal oxide nanoparticles [27][28][29][30], as well as their composites and combinations [31][32][33][34][35], including graphene wrapped-phosphotungstic acid hybrid [36], and the combination of reduced graphene oxide with metal-organic frameworks of Ni with 1,3,5-benzene tricarboxylic acid [37]. An original approach for the simultaneous quantification of sunset yellow FCF and tartrazine has recently been developed using a paper-based electrode (conductive ink based on graphite powder and nail polish supported on cardboard) [38].…”
Section: Introductionmentioning
confidence: 99%
“…The authors indicated that the high sensitivity below 0.09 µmol/L was due to the larger pore size found at the higher sintering temperature and pH, which presents a good development at high temperatures of 70 o C [18]. One of the few reports where combined metal oxides were used to detect SY-TZ used Fe and Si [19], but combined with carbon nanotubes, where the authors achieved a detection limit of less than 0.09 µmol/L, very close to the detection limit reported in this study. The reason for studying these dyes in foods is the same reason that motivated the studies reported above.…”
Section: Introductionmentioning
confidence: 99%
“…Their figures of merit are summarized in Table 1. In a number of cases, simultaneous detection of SY FCF with tartrazine [46,47,49,50,[54][55][56]58] has been achieved. However, the analytical characteristics and detection sensitivity can be further improved.…”
Section: Introductionmentioning
confidence: 99%